Profile of second-level students exempt from studying Irish - Merike Darmody; Emer Smyth (The Economic and Social Research Institute (ESRI), 2016)
Drawing on curriculum differentiation theory, this paper discusses exemptions from learning Irish granted to Irish post-primary students. In order to explore the profile of students granted such exemptions, the study utilises data from a national longitudinal study, Growing Up in Ireland. Additional information is provided by administrative data collected by the Department of Education and Skills to show trends in the number of exemptions granted over time. The findings show that factors impacting on being exempt include gender, social class, having a special educational need at primary school and being born outside Ireland.
Keywords: 330; post-primary schools; curriculum differentiation; exemptions from Irish; Ireland